1976
DOI: 10.1007/bf02532900
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopathogenicity of rapeseed oils and oil blends differing in erucic, linoleic, and linolenic acid content

Abstract: Male Wistar rats were fed semipurifed diets containing 20% fat for 25 weeks. Ten different oils or oil blends were employed, including rapessed oils, simulated rapeseed-type oils, and modified rapeseed-type oils. Safflower, soybean, and hydrogenated coconut oils served as control oils. Histopathological examination of the cardiac tissue was conducted at the end of the study and an incidenceseverity rating assigned to the lesions induced by each fat. Oils containing high levels of erucic acid (26-30%) induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 12 publications
0
18
1
1
Order By: Relevance
“…In contrast, myocardial Iesions found in male rats are often necrotic and fibrotic whether they have been fed a control diet, or a RSO high or low in erucic acid (Kramer et al . 1973;McCutcheon et al . 1976: Vles et al 1976;Hulan et al 1911a,b,c (Hulan et al 1977 c).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, myocardial Iesions found in male rats are often necrotic and fibrotic whether they have been fed a control diet, or a RSO high or low in erucic acid (Kramer et al . 1973;McCutcheon et al . 1976: Vles et al 1976;Hulan et al 1911a,b,c (Hulan et al 1977 c).…”
Section: Methodsmentioning
confidence: 99%
“…Different authors [ 1 ] have indicated that car diovascular damage might be caused by di etary lipids. Thus, both linolenic (18:3 n-3) and erucic (22:1 n-9) acids have been ac cused of causing irrepairable damage in the cardiac tissue [2].…”
Section: Introductionmentioning
confidence: 99%
“…The specific role of 18:3 n-3 of LEAR oil in the etiology of cardiac necrosis was postulated by McCutcheon et al (1976) and Trenholm et al (1979) Clandinin, 1980;McMurchie et aL, 1983;Rocquelin et aL, 1986;McMurchie, 1988). Preliminary results in our laboratory (Grynberg et al, 1984) …”
Section: Resultsmentioning
confidence: 98%